Pengaruh Learning Strategy Terhadap Academic Achievement pada Mahasiswa Akuntansi - Sany Sany; Martin Kurniadi; Stefani Mariana (Business Accounting Review, 2021)
Today, accounting is regarded as something essential and almost applicable to many aspects.To assure the work quality of future accountants, it’s important to ensure that they enter a propereducational process. So, this study will investigate the relationship between learning strategy andaccounting student’s academic achievement. The lack of research on this subject during pandemic eramakes this topic unique. It’s hoped that this study’s findings can be useful to future accountants andteachers. This research uses 278 Accounting Students data at Petra Christian University, Surabaya,during the study period of August-December 2021 through an online questionnaire. These dataanalyzed using linear regression method through SPSS 25. This study’s findings shows that learningstrategy and academic achievement has a significant positive relationship on accounting student’sacademic achievement. It’s highly recommended for other researchers to further investigate this topicwith a different sample due to the limitations in this study.